Changes in the Competence Profile of HR Specialists in The Era of Digital Economy and Their Importance for The Post-Graduate Education - Anna STANKIEWICZ-MRÓZ (Communications of International Proceedings, 2021)
The strong pressure to the increase of efficiency and the expectation of sustainable human resource management cause that competences in the field of data analytics, digital transformation or automation of HR processes, which could be called “competences 4.0 for HR”, are becoming more and more important. The aim of this study is to identify the competency gap of HR specialists in the context of the ongoing digitization of the economy and to analyze the post-graduate education programs in the field of human resource management – in terms of the presence of subjects that could fill this competency gap. The research used the text data mining of job offers regarding the position of HR specialist. The grouping of competences with the use of the Latent Dirichlet Allocation method was applied. Furthermore, the research with the use of questionnaire among post-graduate students in the field of HRM was carried out. The aim of these tests was to diagnose the perception of the meaning of “competences 4.0 in HR”. Moreover, an analysis of  educational programs within the framework of the post-graduate HRM studies was carried out. The obtained results identify the competency gap concerning digital competences in HR and diagnose the discrepancy between the forecasted HR competences and their development in the process of post-graduate education. Meeting the challenges of HR in the digital economy should have consequence for changes in the process of the post-graduate education
Keywords: HR Specialists; Competence Profile; Digital Economy; Competency Gap; Post-Graduate Education.